2021
DOI: 10.1186/s12864-021-08002-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of the BES/BZR gene family in wheat and foxtail millet

Abstract: Background BES/BZR family genes have vital roles in plant growth, development, and adaptation to environmental stimuli. However, they have not yet been characterized and systematically analyzed in wheat and foxtail millet. Results In the current study, five common and two unique BES/BZR genes were identified by genome-wide analysis in wheat and foxtail millet, respectively. These genes were unevenly distributed on 14 and five chromosomes of wheat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…The total RNA extraction, cDNA synthesis and qRT-PCR analysis were performed as described previously [60]. All primers applied in qRT-PCR were listed in electronic supplementary material, table S11.…”
Section: Methodsmentioning
confidence: 99%
“…The total RNA extraction, cDNA synthesis and qRT-PCR analysis were performed as described previously [60]. All primers applied in qRT-PCR were listed in electronic supplementary material, table S11.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a recent study identified 56 Laccase family members linked to lignin metabolism ( Simões et al, 2020 ). In addition, various other gene families involved in multiple stress responses, disease resistance, seed storage or transport, such as WD40 ( Mishra et al, 2014 ), 14–3-3 ( Kumar et al, 2015 ), ZIP ( Alagarasan et al, 2017 ), SOD ( Wang et al, 2018c ), OASTL ( Liu et al, 2019b ), ATG ( Li et al, 2016a , b ), LIM ( Yang et al, 2019 ), CDPK ( Yu et al, 2018 ), NBS-LRR ( Zhao et al, 2016 ), CNL ( Andersen and Nepal, 2017b ), SSP ( Gaur et al, 2018 ), MADS-box ( Zhao et al, 2021a ), BES/BZR ( Liu et al, 2021 ), SNARE ( Wang et al, 2021a ), and PTI1 ( Huangfu et al, 2021 ; Supplementary Table 3 ). Genome-wide identification and in silico analysis of phosphate transporter 1 gene ( PHT 1 ) in Setaria viridis depicted 12 PHT 1 gene families for phosphorous uptake ( Ceasar, 2019 ).…”
Section: Omics Resources In Setariamentioning
confidence: 99%
“…Thus, the availability of foxtail millet genome information provided excellent opportunity for researchers to initiate whole-genome annotation and perform comparative genomic study in foxtail millet [ 5 ]. Until now, foxtail millet has gained popularity among millet research community and several gene families such as AP2/ERF [ 1 ], GRAS [ 2 ], NF-Y [ 3 ], LecRLKs [ 4 ], NAC [ 6 ], WD40 [ 7 ], MYB [ 8 ], PPR [ 9 ], HSP [ 10 ], CDPK [ 11 ], BES/BZR [ 12 ], and MADS-Box [ 13 ] have been identified and characterized to investigate their role in plant abiotic stress tolerance.…”
Section: Introductionmentioning
confidence: 99%